2011
DOI: 10.1097/aln.0b013e3182023eb7
|View full text |Cite
|
Sign up to set email alerts
|

Routine Clinical Practice Effectiveness of the Glidescope in Difficult Airway Management

Abstract: Introduction:The Glidescope video laryngoscope has been shown to be a useful tool to improve laryngeal view. However, its role in the daily routine of airway management remains poorly characterized. Methods: This investigation evaluated the use of the Glidescope at two academic medical centers. Electronic records from 71,570 intubations were reviewed, and 2,004 cases were indentified where the Glidescope was used for airway management. We analyzed the success rate of Glidescope intubation in various intubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(119 citation statements)
references
References 37 publications
4
112
1
2
Order By: Relevance
“…All of the patients would have agreed to the same technique if another nasal intubation became necessary in future. There was no significant difference in the anaesthetists' median (IQR [range]) satisfaction with the intubation techniques (videolaryngoscope 2 (1-2 [1-6]); fibreoptic intubation 2 (1-3 [1][2][3][4][5][6]), p = 0.34).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…All of the patients would have agreed to the same technique if another nasal intubation became necessary in future. There was no significant difference in the anaesthetists' median (IQR [range]) satisfaction with the intubation techniques (videolaryngoscope 2 (1-2 [1-6]); fibreoptic intubation 2 (1-3 [1][2][3][4][5][6]), p = 0.34).…”
Section: Resultsmentioning
confidence: 96%
“…Over the last decade, numerous indirect laryngoscopes have been introduced into clinical practice and compared with the Macintosh laryngoscope [1][2][3][4][5][6][7]. Most studies have described a significantly better glottic view and a higher success rate in difficult tracheal intubations for the indirect laryngoscopes.…”
Section: Introductionmentioning
confidence: 99%
“…The threat of losing a skill (DL) that remains the most common successful rescue approach following failed indirect intubation attempts is a serious concern. [19][20][21] Again, whether using a tongue depressor, a DL, or a VL, get good at it and stay good!…”
Section: Competencementioning
confidence: 99%
“…Despite this, the intubation with Glidescope TM video laryngoscopy (GVL) was remarkably easy. Glidescope TM video laryngoscopy has been shown to improve glottic view and intubation success in a number of studies [23][24][25][26][27]. One study identified GVL was 98% successful as a primary technique and GVL after failed DL was 94% successful in 2004 cases [27].…”
Section: Discussionmentioning
confidence: 99%